Insight Into the Distribution of Staphylococci and Their Enterotoxins in Cheeses Under Natural Conditions - Bellio, Alberto; Chiesa, Francesco; Gallina, Silvia; Bianchi, Daniela Manila; Macori, Guerrino; Bossi, Dario; Nia, Yacine; Mutel, Isabelle; Messio, Sabine; Hennekinne, Jacques-Antoine; Decastelli, Lucia (Frontiers in Microbiology, 2019)
Staphylococcal food poisoning outbreaks are a major cause of food-borne illness in the European Union and their notification has been mandatory since 2005. Criteria for the enumeration of coagulase-positive Staphylococci (CPS) and the detection of staphylococcal enterotoxins (SEs) in cheese have been set down in Commission Regulation EC 2073/2005. Currently, few information are available about the distribution of SEs in naturally contaminated cheeses, including raw-milk and artisanal dairy products. The aim of this study was therefore to investigate at both the CPS enumeration and the succession of the enterotoxigenic Staphylococcus aureus and produced enterotoxins levels on the rind and the core of a raw-milk semi-hard cheese, produced on farm. The study has been conducted in three steps: I) seven wheels at different time of ripening where tested for the presence of SEs. II) from each wheel, four portions were subsequently sampled from four different areas (peripheral rind, central rind, peripheral core and central core). III) two cheese wheels, characterized by the highest and lowest CPS numbers and SEs quantification, based on the second step of the study, were further analyzed. A significant difference has been observed in the distribution of CPS and SEs in the four areas sampled, irrespectively of the batch and the time of ripening. The results of this study provided a set of previously unknown information on the influence of natural conditions on the distribution of CPS and SEs thereof in the cheese matrix, filling a gap in the understanding of SEs biosynthesis process.